Gas6/AXL pathway: immunological landscape and therapeutic potential - Zhai, Xiaoqian; Pu, Dan; Wang, Rulan; Zhang, Jiabi; Lin, Yiyun; Wang, Yuqing; Zhai, Ni; Peng, Xuan; Zhou, Qinghua; Li, Lu (Frontiers in Oncology, 2023)
Cancer remains a fatal disease and the second leading cause of death worldwide. The inheritance of genetic mutations and somatic mutations is the main cause of cancer development. Currently, many studies have shown that Gas6 plays a rather critical role in cancer. Numerous data suggest that the up-regulation of Gas6/TAM is associated with the development of multiple cancers, such as breast cancer, chronic lymphocytic leukemia, non-small cell lung cancer, melanoma, prostate cancer, etc, and the shortened overall survival. The Gas6/TAM pathway has been reported to be required for cancer cell proliferation and migration. Knockdown of TAM receptors Axl and Mer inhibited tumor cell proliferation and induced the apoptosis. Interestingly, Gas6 also plays a key role in the tumor microenvironment. The Gas6/TAM pathway can affect angiogenesis, the expression of immune-related molecular markers and the secretion of certain cytokines in the tumor microenvironment, and can also regulate the function of a variety of immune cells. In addition, there is evidence that the Gas6/TAM pathway is also involved in tumor therapy resistance and promotes the development of tumor drug resistance through multiple mechanisms. In recent years, an increasing number of studies have begun to explore in depth the importance of the Gas6/TAM pathway as a potential tumor therapeutic target and its broad promise in immunotherapy; therefore, a timely review of the characteristics of the Gas6/TAM pathway and its value in tumor treatment strategies is warranted. In this review, we describe the role of Gas6 and TAM receptors and the Gas6/TAM pathway in cancer development, progression; then we discuss the impact of Gas6/TAM on the tumor microenvironment; finally, we describe recent advances in the relationship between Gas6/TAM and mechanisms of drug resistance to cancer therapy.